Rodzina i ochrona życia poczętego na sesjach nadzwyczajnych ONZ (Kair plus pięć, Pekin plus pięć, Stambuł plus pięć) - Kropiwnicki, Jerzy (Annales. Etyka w Życiu Gospodarczym, 2008)
For me the history of the battle for fundamental values of our civilization began in the mid-1990s. At that time three major conferences took place: the International Conference on Population and Development in Cairo in 1994, the 1995 World Conference on Women in Beijing and the Conference on Human Settlements in Istanbul in 1996. Surprisingly to most governments and international public opinion they became the battlefield of the war of ideas, which was especially significant during the conferences in Cairo and Beijing. The liberal circles fiercely attacked traditional values which constitute the basis of the international order. Among others, it was the right to live and the institutional family which were especially attacked. There was even an attempt to replace the word family with partnership. The Polish delegation for the conference in Cairo was instructed not only to support the idea of strengthening the family as a basic unit of society, but also to insist on accepting the common definition of marriage as a union of a man and women and defend the position that abortion cannot be treated as a method of family planning or birth control. The discussion at the Cairo conference evolved into a battle for the right to kill unborn children as a method of family planning. Among the Holy See and Poland, it was the countries of Latin America and Muslim countries including African Muslim countries that spoke in defence of traditional values. At the Istanbul conference, also thanks to the Polish delegation, the family was acknowledged as a natural subject of housing policy. In the years 1999, 2000 and 2000 three UN special sessions were held: Cairo +5, Beijing +5 and Istanbul +5. The Polish representation played an important role and the instruction for the Cairo delegation was fulfilled and remains valid.Although the documents of UN Special Sessions are not legally binding for the UN member states they are important for UN policy agendas e.g. economic help for third world countries. It is possible to define the problem of famine as a one of the overpopulation and think of sending condoms to the starving as a solution. There is another consequence of such documents and their language: they influence the public opinion and, after some time, they have an impact on rules of law in the UN member states. That consequence indicates the importance of that battle for the quality of life in the contemporary world.